KEKOSONGAN NORMA PENENTUAN BUNGA PINJAMAN FINANCIAL TECHNOLOGY PEER TO PEER LENDING - Tjandra, Antoni (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2020)
Today is the era of the modern economy which is made non-bank financial institutions sector experiencing growth. One form of this development is marked by the emergence of Financial Technology. One of the products of the Financial Technology is Peer to Peer Lending that have business activities provide loans accompanied by interest to the debtor. Currently lending restrictions imposed on the debtor fintech is 0.8% per day (maximum limit), but this maximum interest limit was issued by Asosiasi Fintech Pendanaan Bersama Indonesia (AFPI) which is an association of Fintech organizers. This paper discusses the legal protection of the debtor against the Peer to Peer Lending lending rate. The method used is normative juridical. The collection of legal materials through the literature and qualitative normative analysis. The results of this study aims to determine the legal protection for debtors in the Financial Technology in the Peer to Peer Lending agreement to interest rate loan Peer to Peer Lending determined by Asosiasi Fintech Pendanaan Bersama Indonesia (AFPI).Saat ini adalah jaman dari perekonomian modern yang dimana hal ini kemudian membuat sektor lembaga keuangan bukan bank mengalami perkembangan. Salah satu bentuk dari perkembangan tersebut adalah ditandai dengan munculnya Financial Technology. Salah satu produk dari Financial Technology adalah Peer to Peer Lending yang mempunyai kegiatan usaha memberikan pinjaman yang disertai dengan bunga kepada debitur. Saat ini batasan bunga pinjaman fintech yang dikenakan kepada debitur adalah 0,8% per hari (batas maksimum), namun batasan bunga maksimum ini dikeluarkan oleh Asosiasi Fintech Pendanaan Bersama Indonesia (AFPI) yang merupakan asosiasi para penyelenggara Fintech. Penulisan ini membahas perlindungan hukum terhadap debitur terhadap suku bunga pinjaman Peer to Peer Lending. Metode yang digunakan menggunakan yuridis normatif. Pengumpulan bahan hukum melalui kepustakaan dan dianalisis normatif kualitatif. Hasil penelitian ini bertujuan mengetahui perlindungan hukum bagi debitur dalam Financial Technology di dalam perjanjian Peer to Peer Lending terhadap suku bunga pinjaman Peer to Peer Lending yang ditentukan oleh Asosiasi Fintech Pendanaan Bersama Indonesia (AFPI).